(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
This article focuses on how the Marjory Gordon model improves nursing care in patients with chronic renal failure undergoing hemodialysis. The study, conducted over 5 months at Mount Sinai Hospital, explores the efficacy of this model in identifying and treating prevalent health problems in this patient group. The Marjory Gordon model, known for its holistic and systematic approach to nursing care, was implemented to assess dysfunctional patterns in patients with chronic renal failure. A quantitative, descriptive, cross-sectional research design was used, applying surveys to a sample of 67 patients, ranging in age from 30 to 75 years, both outpatients and inpatients. The results revealed significant improvements in several aspects of patient care, including nutrition, metabolism, elimination, activity, exercise, sleep, rest, and stress management. These findings underscore the importance of adopting a structured, patient-centered approach to nursing care, especially in complex clinical settings such as hemodialysis. The study concludes the need to integrate and socialize care plans based on this model among nursing staff, which could significantly improve the quality of care provided. In addition, it is recommended that nursing staff reinforce and formally adopt these care plans, ensuring more effective and patient-centered care.